A double-blind, randomized, placebo-controlled study assessing the impact of probiotic supplementation on antibiotic induced changes in the gut microbiome - John, Daniel; Michael, Daryn; Dabcheva, Maya; Hulme, Eleri; Illanes, Julio; Webberley, Tom; Wang, Duolao; Plummer, Sue (Frontiers in Microbiomes, 2024)
The human gut microbiome, crucial for health, can be disrupted by antibiotic treatment, leading to various health issues and the rise of antimicrobial resistance (AMR). This study investigates the impact of a probiotic on the gut microbiome's composition and antimicrobial resistance genes (ARGs) content following antibiotic treatment. Conducted as a single-centre, double-blind, randomized, placebocontrolled trial, adults taking oral antibiotics were allocated into a probiotic or placebo group. Evaluations included viable cell enumeration and shotgun metagenomic sequencing for microbiome analysis, along with ARG assessment. At the end of the study, there were significantly higher numbers of lactobacilli and significantly lower numbers of enterobacteria. The alpha diversity remained stable in the probiotic group throughout the study, but significant reductions were observed in the placebo group post antibiotic treatment. There was significant spatial separation in beta diversities between groups at the end of the study. Compared to baseline levels, there was a significant reduction in the abundance of ARGs in the probiotic group at the end of the study, while ARG abundance in the placebo group was comparable with baseline levels at the end of the study. Co-occurrence network analysis observed consistent betweenness centrality and node degree within group in the probiotic group whereas scores decreased in the placebo group. This study suggests that the probiotic may minimise the disruption of antibiotic treatment on the gut microbiome by preserving microbial diversity and reducing ARG abundance.